Penerapan Aplikasi e-Puskesmas dengan Pendekatan HOT-Fit di Kabupaten Siak (Studi Kualitatif) - Nurmala Sari Jambago; Ennimay Ennimay; Yuyun Priwahyuni; Jasrida Yunita; Doni Jepisah (Universitas Muhammadiyah Semarang, 2022)
Background: e-Puskesmas as a Health Information System for Public Health Center based on information technology, can present information accurately, quickly and reliably, so that the information presented can be used for decision making. From the initial survey, the implementation of the e-Puskesmas application experienced problems in the field, namely network constraints, applications that were sometimes not connected to Healthcare and Social Security Agency (BPJS), officers had not been able to feel the benefits of implementing the application, there was no decree to determine the person in charge of the e-Puskesmas and reporting was still being made. Objective this study aims to analyze the implementation of the e-Puskesmas application in Public Health Centers throughout Siak Regency. Methods: Qualitative research uses a case study approach with in-depth interviews and observation. The informants in this study were the person in charge of the e-Puskesmas, entry officers and the Head of the Public Health Center, totaling 15 people. Results: The implementation of the e-Puskesmas application in terms of human resources (HR), organization and technology has not run optimally. Conclusion: There are obstacles in its implementation. Therefore, it is necessary to have a joint commitment between the Dinas Kesehatan and the Puskesmas to overcome the existing obstacles